Retrospective Evaluation of Immediate Impacted Third Molars Autotransplantation After Extractions of Mandibular First and/or Second Molars With Chronic Periapical Lesions - ERDEM, NECİP FAZIL; GÜMÜŞER, ZEYNEP (W B SAUNDERS CO-ELSEVIER INC, 2021)
Purpose: To evaluate the success rate of simultaneous autotransplantation of the immature impacted third molars with the guidance of computer-aided rapid prototyping (CARP) to the place of mandibular first or second molars with extraction indication due to the untreatable radiographic periapical lesions. Patients and Methods: Twelve radiographically and clinically hopeless mandibular first or second molars with periapical lesions of 10 patients between the ages of 15 to 21 were included in this retrospective clinical study. Cone-beam computed tomography (CBCT) images were used to produce the CARP models of the donor impacted third molars. Following the extractions of the mandibular first or second molars with periapical lesions, sockets were curetted and prepared with proper burs until a suitable infraocclusal fit of the CARP models. The donor teeth were transplanted synchronously with their surgical extractions. Postoperatively patients were followed clinically and radiographically in the 3rd and 6th months and every 6th month thereafter for at least 18 months. Clinically, the mobility, periodontal plaque, bleeding on probing, percussion sensitivity, periodontal pocket, vitality, and occlusion, and radiographically, the root resorption, ankylosis, presence of lamina dura, and healing of periapical lesion were assessed. Result: By the end of 12th month, and thereafter, all transplanted teeth were in occlusion and functioning properly with no clinical or radiological signs of pathology. All of the autotransplantation cases involved in this clinical study were successful within a mean follow-up period of 20.4 months with the least one of 18 months. Conclusion: Immediate autotransplantation of the immature third molars to the place of mandibular first or second molars with extraction indication due to the periapical lesion can be a proper treatment option for adolescent patients. (C) 2020 American Association of Oral and Maxillofacial Surgeons.
Keywords: AUTOGENIC TOOTH TRANSPLANTATION; LONG-TERM; ROOT DEVELOPMENT; SURGICAL TEMPLATES; TEETH; PREMOLARS; SURVIVAL; SUCCESS; RATES